Incidence of deep fascial space infections following lower third molar removal. (22nd May 2017) - O'Connor, N.; Besi, E.; Lopes, V.; Malden, N.
Abstract: Aim: The aim of this study is to investigate the incidence of systemic infection in the deep fascial spaces after a third molar extraction of the neck. Material and methods: This article presents a retrospective study of 723 cases of third molar extractions under the care of Edinburgh Dental Institute over a 1 year period (July 2012 to the end of June 2013) and investigates the incidence of systemic infection in the deep fascial spaces of the neck. Results and conclusions: Four (0.5%) out of the 723 cases acquired a deep fascial space infection and required hospitalisation and further treatment. No correlation saw between the development of a deep cervical space infection and age, gender, smoking status, predisposing medical history, difficulty of extraction or experience of operator. Patients are now informed of the low risk of post‐operative deep fascial space infection following lower third molar removal. But there is a need for prospective studies, which would provide reliable and accurate information on the true incidence of this significant post‐operative complication.